ЗАМОНАВИЙ ТАЪЛИМ ПАРАДИГМАЛАРИ ВА ТАЛАБАЛАРНИНГ ИЖТИМОИЙ КОМПЕТЕНТЛИГИНИ РИВОЖЛАНТИРИШ - Курбаниязова, З.К. (SCIENCE and SOCIETY, 2020)
The article presents scientific data on improving the quality of education and the problem of developing students' social competence based on the paradigm of a competency-based approach.
Keywords: paradigm; competence; competence-based approach to education; social competence; quality of education